Multiple pregnancy and solutions to the problem of its complications (a literature review) - M. O. Franchuk; L. M. Malanchuk; O. A. Franchuk (Zaporožskij Medicinskij Žurnal)
Currently, the number of multiple pregnancies has increased all over the world, and therefore it has become one of the urgent problems of modern obstetrics. The rise is due to both the widespread practical application of effective methods for infertility treatment in healthcare and the use of assisted reproductive technologies.